Effect of NIMA-related kinase 2B on the sensitivity of breast cancer to paclitaxel in vitro and vivo - Yahong Wang; Honghong Shen; Quangui Yin; Tongxian Zhang; Ziyu Liu; Wei Zhang; Yun Niu (Tumor Biology)
NIMA-related kinase 2B has been known to be an important centrosome regulatory factor. The aim of this study was to investigate the effect of NIMA-related kinase 2B on the sensitivity of breast cancer to paclitaxel. We detected the expression of NIMA-related kinase 2B messenger RNA in MCF-10 cells, including MCF-10A, MCF-10AT, MCF-10DCIS.com , and MCF-10CA1a. The influence of NIMA-related kinase 2B in nude mouse was also detected. The association between NIMA-related kinase 2B and clinicopathological factors was explored in invasive ductal carcinoma tissues. NIMA-related kinase 2B was lowly expressed in the precancerous cells, MCF-10A and MCF-10AT, and it was highly expressed in carcinomatous cells, MCF-10DCIS.com and MCF-10CA1a. The upregulation of NIMA-related kinase 2B can introduce the growth of MCF-10AT cells, knockdown of NIMA-related kinase 2B could remarkably inhibit cell proliferation in MCF-10DCIS.com and MCF-10 CA1a cells. Comparing the volume of the xenografts in nude mouse, we found that the tumors treated by NIMA-related kinase 2B small interfering RNA associated with paclitaxel were the smallest among all the groups. Expression of NIMA-related kinase 2B messenger RNA was associated with higher histological grades, positive lymph node, and high Ki67 index (>20%). The partial response rates were 75.0% in NIMA-related kinase 2B negative (NIMA-related kinase 2B−) patients and 15.8% in NIMA-related kinase 2B++ patients. The progressive disease rates were 10.0% in NIMA-related kinase 2B− patients and 52.6% in NIMA-related kinase 2B++ patients ( p  = 0.002). Our findings suggested that NIMA-related kinase 2B could play a role in the development and progression of breast cancer. Combination treatment using NIMA-related kinase 2B small interfering RNA and paclitaxel might be a novel potential therapy method for breast cancer.